Cover Image, Volume 11, Issue 8. (August 2017) - Imparato, G.; Casale, C.; Scamardella, S.; Urciuolo, F.; Bimonte, M.; Apone, F.; Colucci, G.; Netti, P. A.
Abstract : The cover image, by G. Imparato et al., is based on the Research Article A novel engineered dermis for in vitro photodamage research, DOI:10.1002/term.2525 .